THE USE OF SONG IN LEARNING PRONUNCIATION - Anggraini, Ira; Bhuana, Gartika Pandu (IKIP Siliwangi, 2022)
This study aims to determine students' perceptions in learning pronunciation through songs. This was a qualitative research method. The participants of this study were 16 tenth grade students from a the vocational schools in Cimahi. Data were collected through questionnaire. The results showed that the students had a good opinion about the use of songs. They thought that it offered a different learning atmosphere, in which it was more relaxed and enjoyable. Besides, it could improve their pronunciation. ThisÂ indicates that the teacher can use song in teaching pronunciation.Â Keywords:Â Pronunciation, Song